The Effect of Metabolic Surgery on the Complications of Diabetes: What Are the Unanswered Questions? - Neff, Karl J.; Le Roux, Carel W. (Frontiers in Endocrinology, 2020)
It is now established that metabolic surgery (also known as bariatric surgery or obesity surgery) is an effective treatment for type 2 diabetes. Data from several randomized controlled trials have shown that surgery, when used as an adjunct to best medical therapy, is superior to medical therapy alone in achieving glycaemic and metabolic treatment targets in diabetes care. This has resulting in metabolic surgery being recommended as a treatment option for type 2 diabetes in national and international diabetes care guidelines. While the superior glycaemic effect of surgery is clear, the effect of surgery on the complications of diabetes is not fully understood. There are observational and epidemiological data that indicate a preventative effect in cohorts who do not have complications at baseline, as well as a positive effect on those with established diabetic kidney disease. However, there is a dearth of randomized controlled studies that specifically examine the effect of surgery on the complications of diabetes. Therefore, we should remain cautious in some cases, especially in those with retinopathy or neuropathy, as there is potential for deterioration of disease post-operatively. Further study is needed on this important topic. A lot is known, but there remain several unanswered questions. This article summarises what we know about the effect of metabolic surgery on the complications of diabetes, poses some unanswered questions, and suggests how we could answer them.